Data-driven efficient synthetic exploration of anionic lanthanide-based metal–organic frameworks. Issue 81 (23rd September 2022) - Kitamura, Yu; Nakamura, Yuiga; Sugimoto, Kunihisa; Yoshikawa, Hirofumi; Tanaka, Daisuke
Abstract : The synthesis of lanthanide metal–organic frameworks with terephthalate (Ln-BDC-MOFs) was investigated using a data-driven approach. Abstract : The synthesis of lanthanide metal–organic frameworks with terephthalate (Ln-BDC-MOFs) was investigated using a data-driven approach. Visually mapping the previously reported synthetic conditions suggested the existence of unexplored search spaces for novel Ln-BDC-MOFs. By focusing on the unexplored chemical reaction space, we successfully synthesized a series of new anionic Ln-BDC-MOFs, KGF-15, which demonstrated potential as luminescent sensors for Cu 2+ ions. This synthetic exploration approach can significantly reduce the experimental effort required to discover new materials.